Removal of Coolant from Effluent Water by Combined Demulsification and Reverse Osmosis - Nurkhairina Izni binti Abdul Ra’of, Nurkhairina Izni (Universiti Teknologi Petronas, 2009)
The purpose of this project is to separate coolant from effluent water by combined demulsification and reverse osmosis. There are several methods in removing oil from wastewater such as ultrafiltration, anaerobic thermophilic fluidized bed reactor (afbr), dissolve air floatation and reverse osmosis. The selected method is chosen in order to prevent fouling of reverse osmosis membrane and to prevent coolant oil from accumulated at the membrane surface. Firstly, a demulsification process is conducted as a pre-step before reverse osmosis by using IMEC Meczym 579 demulsifier. The effect of time, heating temperature and demulsifier dosage was conducted. It can be summarized that the demulsification process is effective by using 30mg/l of demulsifier at temperature of 27°C and six hours time. The coolant oil accumulated after the demulsification process is removedfrom the effluent water. Later, the effluent water that has been separated from coolant oil is sent to reverse osmosis process. The process is done at pressure of 3.7 MPa and temperature of 27.8 °C. After that, total organic carbon, chemical oxygen demand and turbidity tests were conducted to samples of effluent water before demulsification, after demulsification and reverse osmosis. The value obtained from the three tests show that the selected method is a promising method in removing coolant from effluent water